Atmospheric ozonolysis of crotonaldehyde in the absence and presence of hydroxylated silica oligomer cluster adsorption. (October 2021) - Wang, Naixian; Wei, Fenghua; Sun, Jianfei; Wei, Bo; Mei, Qiong; An, Zexiu; Li, Mingxue; Qiu, Zhaoxu; Bo, Xiaofei; Xie, Ju; Zhan, Jinhua; He, Maoxia
Abstract: As one of the main components of combustion of tobacco products occurs (CARB), crotonaldehyde has an acute toxicity and widely exists in the atmosphere, which is harmful to human health. The removal efficiency of VOCs by ozonation can reach 80–90%. Based on the theory of quantum chemistry, the degradation mechanism, kinetics and toxicity of crotonaldehyde by ozonation in gas phase and heterogeneous phase were studied. Ozone was added to the olefins unsaturated double bond to form a five-membered ring primary ozonide, which was further fractured due to its unstable structure to form a Criegee intermediate and an aldehyde compound. The reaction rate constant of crotonaldehyde with ozone was 1.24 × 10 −17  cm 3 molecule −1 s −1 at 298 K and 1 atm, which was an order of magnitude higher than the experimental value. From toxicity assessment, it was found that the ozonation of crotonaldehyde is beneficial to the removal of toxicity. Mineral dust aerosol exists in the atmosphere in large quantities, and SiO2 is the most abundant component. VOCs are transformed into particle state on their surface through homogeneous nucleation and heterogeneous nucleation. Referring to the crystal structure of SiO2, five hydroxylated silica oligomer cluster structures were simulated and the adsorption configurations of crotonaldehyde on their surface were simulated. The adsorption of crotonaldehyde on the surface of the clusters was achieved by forming hydrogen bonds and had good adsorption effects. The adsorption of hydroxylated silica oligomer clusters didn't change the ozonation mechanism of crotonldehyde, but had a certain effect on the reaction rate. Graphical abstract: Image 1 Highlights: The mechanisms and toxicities for the gas-phase of TCA with ozone were studied. Risk assessment showed that the ozonation of TCA was beneficial to the removal toxicity. The silanol clusters have good adsorption effect on TCA by form the hydrogen bond interaction. The order of the five adsorption configurations is ADS5-TCA > ADS4-TCA > ADS3-TCA3 > ADS6-TCA > ADS1-TCA. The adsorption of silanol doesn't change the reaction mechanism, but effects on the reaction rate.